2010
DOI: 10.4097/kjae.2010.59.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Dose of remifentanil for minimizing the cardiovascular changes to tracheal intubation in pediatric patients

Abstract: BackgroundThe purpose of this study was to investigate a dosage of remifentanil for attenuating cardiovascular changes during anesthetic induction in pediatric anesthesia.MethodsWe examined the effect of remifentanil on the cardiovascular responses to intubation in 90 children ASA 1 patients, aged 4-15 years, randomly allocated to receive 1.0 ug/kg remifentanil as a bolus (R 1), or 1.5 ug/kg remifentanil (R 1.5), or 2.0 ug/kg remifentanil (R 2). Before induction, IV midazolam 0.05 mg/kg was given for sedation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…effectively attenuate the sympathetic response, even the prolongation of the QTc (the heart rate-corrected distance between the beginning of the QRS wave and the end of the T wave in the electrocardiography) interval [6], to laryngoscopy, endotracheal intubation [7][8][9], and incision [10,11]. According to recent studies, remifentanil (1 lg/kg), in combination with thiopental and rocuronium, is more effective than lidocaine (1.5 mg/kg) and esmolol (1 mg/kg) for blunting the haemodynamic responses to intubation in normotensive adults [12], and a bolus dose of 2 lg/kg remifentanil was enough to attenuate the sympathetic response in pediatric patients aged 4-15 [13]. In a very recent study, Cafiero et al recommended the use of remifentanil infusion (0.25 lg/kg/min) in patients with risk factors for dysrhythmias, as it prevents the increase in the QT (the distance between the beginning of the QRS wave and the end of the T wave in the electrocardiography) dispersion after intubation in comparison with fentanyl [14].…”
Section: Introductionmentioning
confidence: 99%
“…effectively attenuate the sympathetic response, even the prolongation of the QTc (the heart rate-corrected distance between the beginning of the QRS wave and the end of the T wave in the electrocardiography) interval [6], to laryngoscopy, endotracheal intubation [7][8][9], and incision [10,11]. According to recent studies, remifentanil (1 lg/kg), in combination with thiopental and rocuronium, is more effective than lidocaine (1.5 mg/kg) and esmolol (1 mg/kg) for blunting the haemodynamic responses to intubation in normotensive adults [12], and a bolus dose of 2 lg/kg remifentanil was enough to attenuate the sympathetic response in pediatric patients aged 4-15 [13]. In a very recent study, Cafiero et al recommended the use of remifentanil infusion (0.25 lg/kg/min) in patients with risk factors for dysrhythmias, as it prevents the increase in the QT (the distance between the beginning of the QRS wave and the end of the T wave in the electrocardiography) dispersion after intubation in comparison with fentanyl [14].…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 14 Several studies have shown that remifentanil causes cardiovascular compromise during induction, which in turn alleviates the sympathetic stimulation caused by endotracheal intubation. 15 These studies proved that remifentanil decreases the systemic circulation. Therefore, continuous infusion of remifentanil at different doses affects neuromuscular pharmacodynamics.…”
Section: Discussionmentioning
confidence: 91%
“…The flow chart of the literature search and study selection is shown in Figure 1. We identified 31 articles but only 16 publications met our criteria [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Details of drugs used, dosage, route, observations and cardiac rhythm disturbances related to the response are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…One study 16 documented the changes as more than 30% change from baseline and one study 15 measured the percentage change in BP and HR. Eight studies 8,[10][11][12]14,18,21,23 presented results as graphs alone.…”
Section: Resultsmentioning
confidence: 99%